The dual role of neutrophils in sepsis-associated liver injury - Fang, Lexin; Song, Yu; Chen, Jiangtao; Ding, Yueping (Frontiers in Immunology, 2025)
Sepsis is often accompanied by liver injury and is associated with an increase in the number of circulating and hepatic neutrophils. In sepsis-associated liver injury, neutrophils exhibit phenotypic heterogeneity and perform both pro- and anti-inflammatory functions. Moreover, neutrophil dysfunction and neutrophil-associated immunosuppression are also involved in the pathogenesis of sepsis. Given the complex functionality of this cell type, the aim of this review was to describe the possible mechanistic role of neutrophils in sepsis-associated liver injury, with a brief introduction to neutrophil recruitment and subsequent discussion of the potential contributions of neutrophils to different subtypes of sepsis-associated liver injury.